LEGAL PROTECTION FOR HOLDERS OF LAND OWNERSHIP CERTIFICATES IN CASES OF LAND FREEZING BY THE NATIONAL LAND AGENCY - Suparman Budi Cahyono; Tahegga Alfath Primananda; Heru Kuswanto (SOSIOEDUKASI, 2026)
Land freezing is an administrative action to maintain the status quo over disputed land. However, in practice, it is often filed unilaterally by third parties without a clear legal basis, potentially harming certificate holders and creating legal uncertainty. This research aims to analyze the conformity of land freezing implementation with statutory provisions and to examine legal protection for holders of land title certificates against freezing actions filed by third parties. A normative legal research design underpins the present study, which proceeds by way of both a statutory approach and a case based approach. The UUPA, the Government Regulation on Land Registration, and the Minister of ATR or BPN Regulation concerning freezing and seizure serve as the primary legal materials. Secondary materials are obtained from legal literature. The results show that the regulation on land freezing still contains normative obscurity, particularly regarding the requirements and limitations on parties who may file freezing requests, thereby opening opportunities for third parties to carry out unilateral freezing without a strong legal basis, which ultimately creates conflict and legal uncertainty for land title certificate holders, and that the existing mechanisms have not fully provided adequate legal protection since freezing can hinder right holders from performing legal acts over their land. Therefore, clearer and more assertive legal regulatory improvements and enhanced supervision in the implementation of land freezing are needed to ensure legal certainty and protection for land right holders.